2013
DOI: 10.1016/j.bbagen.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

PLIN2, the major perilipin regulated during sebocyte differentiation, controls sebaceous lipid accumulation in vitro and sebaceous gland size in vivo

Abstract: Background Lipid synthesis and storage are accomplished by lipid droplets (LDs). The perilipin family of LD-associated proteins, comprising 5 members (PLIN1-PLIN5), has been well characterized in adipocytes but not in sebocytes, epithelial cells in which LD formation is a key feature of the cellular differentiation. Methods Perilipin expression in the sebaceous gland cell line SZ95 and in human sebaceous glands was studied by qRT-PCR, Western blots, and immunohistochemistry. Lipid accumulation was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 34 publications
6
52
0
1
Order By: Relevance
“…We showed previously that PLIN2 expression is regulated during sebocyte differentiation and is important for lipid accumulation in vitro and for regulating SG size in vivo (18). PLIN3 expression was higher than that of PLIN2, but did not change as sebocytes differentiate (18).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…We showed previously that PLIN2 expression is regulated during sebocyte differentiation and is important for lipid accumulation in vitro and for regulating SG size in vivo (18). PLIN3 expression was higher than that of PLIN2, but did not change as sebocytes differentiate (18).…”
Section: Introductionmentioning
confidence: 79%
“…We showed previously that PLIN2 expression is regulated during sebocyte differentiation and is important for lipid accumulation in vitro and for regulating SG size in vivo (18). PLIN3 expression was higher than that of PLIN2, but did not change as sebocytes differentiate (18). Initially identified as a protein involved in the recycling of the mannose 6-phosphate receptor and termed TIP47 for 'tail-interacting protein of 47 kDa (19), PLIN3 was localized by Wolins and colleagues to nascent LDs (20).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of PPARβ/δ affects many cellular process, including glucose metabolism, fatty acid metabolism, and keratinocyte, 19,20) adipocyte and sebocyte differentiation. 21) We focused on the ability of PPARβ/δ activation to induce differentiation. It has also been reported that mice have epithelial stem/ progenitor cells, as do humans.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial role of sebum (innate immunity) SZ95 [58][59][60][61][62][63] SEB-1 [64] Expression and regulation of sebocyte lipid droplet-associated proteins SZ95 [50,[65][66][67] Seb-E6E7 [50] Mechanisms of IGF-1-mediated stimulation of sebaceous lipogenesis SEB-1 [68,69] SZ95 [70] Actions of peroxisome proliferator-activated receptors in sebocytes SEB-1 [71] SZ95 [72][73][74] Actions of endocannabinoids in sebocytes SZ95 [75] Mechanisms of retinoid-mediated inhibition of sebaceous lipogenesis SZ95 [39,76] SEB-1 [77][78][79] Expression of steroidogenesis-related enzymes and regulation of local androgen synthesis SZ95 [40,80] SEB-1 [41] SEBO662 [44] Mechanisms of apoptosis in sebocytes SZ95 [81] SEB-1 [41] Cutaneous functions of the vitamin D system SZ95 [82,83] Regulation of sebaceous lipogenesis by microRNAs SZ95 [49] Neuropeptide synthesis and their action on sebocytes SZ95 [84,85] molecular and cellular processes underlying sebaceous lipogenesis and their perturbation in SG diseases (Table 1). Recent examples of fields pushed forward by employing immortalized human SG cell lines include the analysis of sebocyte adipokines, [48] the identification of microRNAs associated with sebaceous differentiation, [49] and the study of the proteins associated with cytoplasmic SG lipi...…”
Section: Cell Line Referencesmentioning
confidence: 99%